Green synthesis, characterization, and photocatalytic activity of cobalt chromite spinel nanoparticles - Saeid Taghavi Fardood; Reza Forootan; Farzaneh Moradnia; Zolfa Afshari; Ali Ramazani (Materials Research Express, 2020)
Eriochrome Black T, an azo dye, was degraded under visible light irradiation using CoCr _2 O _4 nanoparticles as a photocatalyst. In this study, CoCr _2 O _4 cubic-spinel nanoparticles were synthesized via a novel and green sol-gel method. The synthesized sample was characterized by EDX, XRD, TEM, FESEM, DRS, and FTIR. The CoCr _2 O _4 NPs have good photocatalytic activity for degradation of Eriochrome Black T (EBT) dye at room conditions so that 90% of EBT was degraded in 90 min under the visible light. The CoCr _2 O _4 NPs reusability was scanned and confirmed that the nano-photocatalyst shows a few declines in its activity after the three runs.